Analysis Of Computational Thinking Abilities Of High School Students Based On Self-Regulated Learning - Sidik, Nadia Hanifah; Khusna, Hikmatul (JTMT: Journal Tadris Matematika, 2024)
There is a phenomenon where students with moderate ability can achieve the highest rank in the class, while students with high intelligence often have difficulty or failure in their academic achievement. This suggests that students' abilities, no matter how high, will be limited if they are not able to self-regulate their learning. A descriptive qualitative research method was employed in this study, conducted in the XI MIPA class at a public high school in Bekasi. The research subjects were selected based on their SRL levels, categorized as high, medium, and low. Data were collected through interviews and CT tests, using data collection techniques such as observation, tests, and interviews. The results showed that students with high SRL levels excelled in all aspects of computational thinking assessment. Conversely, students with medium SRL levels only demonstrated abilities in three out of four indicators: decomposition, abstraction and generalization, and pattern recognition. Meanwhile, students with low SRL levels only showed abilities in one indicator, which was pattern recognition